Unusual bismuth-containing surface layers of III-V compound semiconductors - Ahola-Tuomi, Marja (fi=Turun yliopisto|en=University of Turku|, 2013)
The understanding and engineering of bismuth (Bi) containing semiconductor surfaces are signi cant in the development of novel semiconductor materials for electronic and optoelectronic devices such as high-e ciency solar cells, lasers and light emitting diodes. For example, a Bi surface layer can be used as a surfactant which oats on a III-V compound-semiconductor surface during the epitaxial growth of IIIV lms. This Bi surfactant layer improves the lm-growth conditions if compared to the growth without the Bi layer. Therefore, detailed knowledge of the properties of the Bi/III-V surfaces is needed. In this thesis, well-de ned surface layers containing Bi have been produced on various III-V semiconductor substrates. The properties of these Bi-induced surfaces have been measured by low-energy electron di raction (LEED), scanning-tunneling microscopy and spectroscopy (STM), and synchrotron-radiation photoelectron spectroscopy. The experimental results have been compared with theoretically calculated results to resolve the atomic structures of the studied surfaces. The main ndings of this research concern the determination of the properties of an unusual Bi-containing (2×1) surface structure, the discovery and characterization of a uniform pattern of Bi nanolines, and the optimization of the preparation conditions for this Bi-nanoline pattern.